Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean. Issue 10 (26th July 2016) - Li, Hongying; Zhou, Zhiguang; Li, Pengju; Zhang, Da; Liu, Changfeng; Zhao, XiaoQi; Chen, Lizhen; Gu, Congnan; Lin, Tingting; Hu, Mengmeng
ABSTRACT: The eastern segment of the Central Asian Orogenic Belt is traditionally called the Xing'an Mongolia Orogenic Belt (XMOB). Ordovician intrusive rocks exposed in the XMOB, from north to south, are the Abaga-East Ujimqin Qi-Duobaoshan belt, the Sonid Zuoqi-West Ujimqin Qi belt, and the Damaoqi-Baimaimiao-Tulinkai belt, respectively. Zircon U–Pb dating and geochemical data are presented for the intrusive rocks in East Ujimqin Qi and West Ujimqin Qi, Inner Mongolia. The intrusive rocks from East Ujimqin Qi consist of gabbro, diorite, and granodiorite. LA-MC-ICP-MS zircon U–Pb ages range 446 to 461 Ma. Geochemical data suggest that the gabbros and diorites from East Ujimqin are a tholeiitic series, both of arc-related and N-MORB (mid-ocean ridge basalt) signature, indicating a back-arc basin setting. The granodiorites have a shoshonitic series and arc-related signature. Rare earth element (REE) patterns and trace element characteristics suggest gabbros, diorites, and granodiorites are petrogenetically correlated. These intrusive rocks from East Ujimqin Qi have high light REE, Th, and U concentrations, suggesting the effect of middle–upper continental crustal contamination. Major oxides display positive or negative correlations, with increasing MgO or SiO2, indicating that fractional crystallization occurred during magma evolution. Geochemical data of diorite from West Ujimqin Qi indicate a tholeiitic series, arc-related signature. Zircon U–Pb dating yielded an age of 441.8 ± 1.5 Ma. Integrated with the regionally exposed Mid–Late Ordovician plutons and metasedimentary strata, we concluded that the northward subduction of the Palaeo-Asian Ocean (PAO) that occurred beneath the southern margin of the South Mongolian Micro-continent along the Sonid Zuoqi-Xilinhot gave rise to early Palaeozoic igneous rocks from the Abaga–East Ujimqin Qi–Duobaoshan and the Sonid Zuoqi–West Ujimqin Qi belts. Southward subduction beneath the North China Craton generated the Damaoqi–Baimaimiao–Tulinkai belt. The results support the bidirectional subduction model of the PAO in the early Palaeozoic.